Influence of Land Use Regulatory Instruments on Household Disaster Risk Management in Eldoret Urban Area - Ong’anya, Dedana O.; S., Samuel (African Journal of Education,Science and Technology (AJEST), 2019)
Land use planning seeks to regulate land use in efficient manner, thus preventing escalation of hazards into disaster risks that would threaten lives of households in both rural and urban areas. Thus, it enables households in urban areas to access serviced land at affordable prices, access socio-economic services, infrastructure, transportation facilities and good environment. The demand for urban serviced land is often in the increase, and this has been enhanced by natural population growth and rural-urban migration. This study examined the influence of urban land use planning regulatory instruments on household disaster risk management in EUA. Descriptive Survey research designs were used. The classical spatial economic theory (making room model); stakeholders’ theory and disaster reduction theory (community-based model) were applied in this study. The study targeted the households in Eldoret Urban Area of (Langas, Kapsoya, Kamukunji and Kapsaos). Proportional stratified random sampling was applied for the purpose of quantitative data collection, while, purposive sampling was used for qualitative data. A total sample size of 550 respondents was sampled. Questionnaire was the main instruments to collect primary data, alongside key informant interviews (KIIs) and focus group discussions (FGDs). Finally; descriptive, inferential, regression and correlation statistics were applied in data analysis and interpretation. Results indicated that land use planning regulatory instruments have combined influence of 69.0% over disaster risk management. Test results on H01 showed that there was significantly positive relationship between urban land use planning and disaster risk management. The effect of Land use planning regulatory instrument on HDRM was significant positive (R= 0.878), the study revealed that Land use planning regulatory instrument accounted for 87.8% (R2 =.771) of HDRM. The findings are a pointer to the fact that land use planning and its three dimensions had significantly positive effects on household disaster risk management. From these results, it can be concluded that urban land use planning is a critical tool or technique in designing and developing urban areas where hazardous zones are mapped, demarcated and kept off from households’ socioeconomic activities. It was recommended that urban authorities must focus on urban land use planning to achieve sustainable development and growth.